The Global Curriculum: Rethinking School from the Perspective of Education - Pablo Del Río; Amelia Álvarez (Networks: An Online Journal for Teacher Research, 2004)
This paper brings together educational proposals based on a framework derived from the perspectives of historic-cultural and genetic-cultural theory. This framework enables us to specify the goals, realities and alternatives for renewal in the educational task, and to highlight a series of recommended reorientations for tackling education in a changing world. These reorientations imply a switching of attention: from the current emphasis on knowledge as an end in itself, towards a greater attention to the tools and operators of knowledge; from an emphasis on individual tasks to a greater concern with shared activities as the origin of mental operations; and from an emphasis on meaning and knowledge as ends to an emphasis on meaning and knowing as means. In general the need to adopt a more evolutionary, dynamic and integral vision of the educational process is highlighted here, one in which the development of the person and the functional personality takes priority over the accumulation of repertories of different forms of knowledge. In the same spirit, we advocate the adoption of a vision of the whole developmental process in culture as a global curriculum, in which school should take the role of articulating structuration and meaning.
Keywords: global curriculum; genetic-cultural development; meaning; school commitment